2005
DOI: 10.1002/fld.1125
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of settling of a large solid particle during bioconvection

Abstract: SUMMARYSettling of a large solid particle in bioconvection ow caused by gyrotactic microorganisms is investigated. The particle is released from the top of the bioconvection chamber; its settling pattern depends on whether it is released in the centre of the bioconvection plume or at its periphery. The Chimera method is utilized; a subgrid is generated around a moving particle. The method suggested by Liu and Wang (Comput. Fluid 2004; 33:223-255) is further developed to account for the presence of a moving bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Geng and Kuznetsov [10,11] investigate the sedimentation of small solid particles in bioconvection. Sedimentation of a single large particle during bioconvection is studied in Reference [12].…”
Section: P Geng and A V Kuznetsovmentioning
confidence: 99%
See 1 more Smart Citation
“…Geng and Kuznetsov [10,11] investigate the sedimentation of small solid particles in bioconvection. Sedimentation of a single large particle during bioconvection is studied in Reference [12].…”
Section: P Geng and A V Kuznetsovmentioning
confidence: 99%
“…At the surface of the settling particles, the no-slip boundary condition is imposed. Geng and Kuznetsov [12] have shown that the values of the streamfunction and vorticity on a moving boundary in a multi-connected domain can be calculated numerically by the following procedure.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%